ANALYSIS OF INNOVATION MANAGEMENT SYSTEMS IN INTERNATIONAL COMPANIES - Tugonov Ibrohimkhodja; Mardiyev Bunyod (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In modern globalisation, international companies encounter numerous challenges in managing their operations effectively. The swift pace of technological advancement, evolving consumer preferences, and increasingly complex regulatory environments are among the key hurdles that must be addressed to maintain market competitiveness. In recent years, the management approaches of major global corporations have undergone substantial transformation, driven by technological innovation and dynamic market conditions. To stay competitive, these organisations must embrace modern management systems that support sustainability, digital transformation, project oversight, and cross-cultural coordination. Implementing such systems demands considerable financial investment and a readiness to adapt to change. This article explores the core challenges international companies face in managing their business activities.